THE CONCEPT OF PILGRIMAGE IN THE CULTURE OF LATGALE - Juško-Štekele, Angelika (Via Latgalica, 2014)
The aim of the paper is to characterize pilgrimage as a significant concept in Latgalian culture by emphasizing pilgrimage’s dialectic comprehension and most essential manifestations in culture. The study use a linguistically culturological approach and reviews pilgrimage as a global and multilevel structure, that consists of conceptual, emotively evaluated, historical and etymological layers (Степанов 2001: 84). For this purpose there were used mainly such written sources as vocabularies, periodicals and fiction, that refer to pilgrimage.While gathering various interpretations of sacredness and journeys, paper deals with four main comprehensions of pilgrimage in Latgale: firstly, pilgrimage as a religious activity, that means walking to a sacred place along with the prayers, secondly, pilgrimage as a social campaign for the affirmation of ideological efforts, thirdly, pilgrimage as an individual and sensitive search for the eternal values and, lastly, pilgrimage as a type of a religious tourism in contemporary post-modern society.The beginning of Catholic pilgrimage tradition in Latgale usually tends to be associated with Aglona, when Dominicans or the so called White Fathers Order began their activities in the region in 1699. Today, within the Rēzekne–Aglona diocese of the Roman Catholic Church, there are several sites, which have been officially acknowledged as sacred on the basis of the corresponding features they possess. Primarily, it’s the altarpiece of the Virgin miracle-worker and other relics, that are special for the Christianity and where pilgrims may pray for health or any other mercy. Secondly, in the territory of the sacred place there may be located objects of nature, that bring health and blessing, for example, sacred spring.The appreciation of religious pilgrimage in Latgalian culture has been also affected by the historical context. From 1918 to 1940 pilgrimage activity experienced especially strong prosperity, but it changed during the Soviet-era, when pilgrimage subject in mass media was forbidden and lost its official support, but it still continued to proceed. Organized pilgrimages to Aglona recurred only in 1989 along with the so called Third Latvian National Awakening.Pilgrimage in Latgalian culture appears also as a social campaign for the affirmation of ideological efforts, where comprehension of sacredness from the scope of the Christian Religion transfers into secular every-day lifestyle and subjects to ideological dogmas of era. Such interpretation of pilgrimage especially activates during 1920s–1930s, as well as in 1940s and 1990s. The aspiration for such pilgrimage usually is a place, person or monument, but all pilgrimages that are distinctive to the affirmation of ideological efforts possess fragmentation feature. With the alterations within the ideological emphasis the idea of the ideological pilgrimage either disappears either transforms into ceremonial procession or simple memorial tribute.Comprehension of the pilgrimage as an individual and sensitive search for the eternal values is more related to the individualized pilgrim’s motive, that is connected to emotional experience, namely, search for the deprecated and irreversible values. This motive is especially noticeable within the exiled Latgalians’ literature, where such personages as motherland, home, mother and mother’s tomb are united and related to the Virgin’s archetype. The pilgrimage process, that Latgalian exiled writers live through in their imagination, shows, that it is one of the most essential values, that is evaluated during the immense influence of foreign countries, that helps to preserve Latgalian identity at times while far away from home.One of the most popular type of tourism today is religious tourism. In Latgale it began in the 20th century through periodicals of 1920s–1930s. Now it is an integral part of the global tourism industry, including both national and international projects.Meaning diversification in the contextual semantics of the pilgrimage shows its deep roots in the Latgalian culture and how it merges universal, national, ethnic and denominational characteristic marks in cultural traditions.